Peningkatan Prestasi Belajar Siswa melalui Penerapan Model Pembelajaran Problem Based Learning pada Siswa Kelas XI IPA SMA Negeri 2 Pujut - Nurelam, Nurelam (Jurnal Ilmiah IKIP Mataram, 2023)
The purpose of this study was to determine the increase in student achievement by applying problem based learning. This study uses action research (action research) as much as two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The target of this research is students of class XI IPA1 SMAN 2 Pujut. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student achievement increased from cycle I to cycle II. In the first cycle, the average score was 70 with 54% classical completeness, increased in the second cycle with an average score of 82 with a 96% classical completeness percentage. This learning model can be used as an alternative to learning Physics in class.